PROCESS OF DEVELOPMENT OF MODEL BASED ON LINEAR PROGRAMMING TO SOLVE RESOURCE ALLOCATION TASKS WITH EMPHASIS ON FINANCIAL ASPECTS - Veselovska, Lenka (European Scientific Journal, ESJ, 2014)
Article deals with the topic of Linear Programming application on tasks of allocating limited resources in production companies. These restrictions come from both inside of company and market conditions. There is usually limited amount of resource available on market. Moreover the purchase price is also an important decisive factor when estimating the optimal amount of resource needed. The objective of article is to present the process of development of two models based on linear programming which describe situations production companies have to face in terms of resource allocation. We chose to look into this problem from financial point of view. Therefore most important parameters in models are of financial nature. We look into resource allocation in terms of possible costs and revenues. These two models describe the two possible optimization problems – the minimizing tasks and the maximizing tasks. Examples of such tasks from managerial practice are also included.